Hepatocyte targeting using pegylated asialofetuin-conjugated liposomes. (April 2014) - Detampel, Pascal; Witzigmann, Dominik; Krähenbühl, Stephan; Huwyler, Jörg
Abstract Background and purpose: The hepatocyte asialoglycoprotein receptor mediates uptake of desiaylated glycoproteins by receptor-mediated endocytosis. This work explores a hepatocyte-specific targeting strategy using asialofetuin (AF) covalently coupled to pegylated liposomes. Methods: AF was conjugated to the distal end of polyethylene glycol–functionalized phospholipids. Chemical modification of AF did not interfere with its receptor interaction. AF-liposomes had a size of less than 130 nm, were judged to be monodisperse and were labelled with fluorescent organic dyes or loaded with quantum dots. Results: In vitro, binding and cellular uptake of fluorescent AF-liposomes by HepG2 hepatocellular carcinoma cells were reduced at low temperature and could be competitively inhibited by an excess of unbound AF. Hepatocyte-specific targeting and internalization of AF-liposomes in vivo was confirmed in the rat and could be competitively inhibited by co-injection of unbound AF. In contrast, non-pegylated liposomes accumulated in cells of the reticuloendothelial system such as hepatic Kupffer cells and spleen after intravenous administration. Conclusion: We conclude that the use of AF-conjugated, pegylated liposomes is a promising strategy to avoid the reticuloendothelial system and specifically target hepatocytes via the asialoglycoprotein receptor in vitro as well as in vivo.